A DFT Study of The Sensing and Adsorption of Graphene Nanoribbons for DNA Sequencing - Ahmed T. Khudhair ,; Falah H. Hanoon, (University of Thi-Qar Journal of Science, 2021)
Because of its chemical and physical properties, the graphene nanoribbons(GNR) are utilized in the production of accuracy sensors. In this paper, the thickness utilitarian hypothesis Density Functional Theory (DFT) with the B3LYP level, and by utilization of the Gaussian 09 arrangement of projects, was used to explore the adsorptive and detecting ability of DNA on the unblemished nanoribbon. The detecting capacity of these structures was determined as far as a variation of band hole vitality after cooperation among GNR and DNA. Because of counts, it was discovered for GNR that the electronic properties are firmly delicate to the nearness of the DNA particle. In this way, we accept that GNRs can be utilized in sensor gadgets.